Koncepcja i typologia projektów logistycznych - Kasperek, Marek (Concept and Typology of Logistic Projects, 2008)
The article shows the major problem of Logistic Project's definition. The first part of this article focuses on the character and definition of logistic project. The second part describes the typology of logistic project, especially on other kind of logistic project.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 28-37